Pulse energy scalable all-PM dispersion managed figure-9 Yb-doped fiber laser with two distributed gain fibers - Han Zhang; Handing Xia; Junwen Zheng; Jianbin Li; Yaohui Zhang; Fan Zhang; Mengqiu Fan; Xiangjun Xiang; Xiaocheng Tian; Zhimeng Huang; Rui Zhang; Ping Li; et al. (Results in Physics)
We demonstrate an improved layout of an all-polarization maintaining (PM) dispersion managed figure-9 ytterbium (Yb)-doped fiber oscillator with two distributed gain fibers. By adjusting the pump power of the two gain fibers, a stable pulse train with a repetition rate of 45.2 MHz and an average power of 104.17 mW can be obtained, corresponding to a pulse energy of 2.3 nJ. The output pulses can be de-chirped as short as 118 fs. The structural improvement increases the output pulse energy by more than three times compared to the conventional structural type with single YDF. In addition, the self-starting characteristics of the oscillator under different pumping conditions are experimentally studied. It is revealed that increasing the gain level of the NALM while reducing the absorption loss of the additional gain fiber is an effective way of achieving fast self-starting mode-locking driven by only one pump source. This work provides a new perspective for the design and development of figure-9 fiber lasers with high stability and high pulse energy.